Paraprofessionals use of group school‐based instrumental mentoring: Examining process and preliminary outcomes. Issue 9 (7th July 2020) - Strait, Gerald G.; Turner, Jenna; Stinson, Diana; Harrison, Samanthia; Bagheri, Rojan; Perez, Tanya; Smith, Bradley H.; Gonzalez, Jorge; Anderson, Jacqueline R.; Simpson, Jill; D. McQuillin, Sam
Abstract: Many schools use paraprofessionals to implement and monitor interventions. Though paraprofessionals are cost‐effective, many questions remain about the training and skills they need to implement a wide array of school‐based interventions. In this study, we compare paraprofessionals' (i.e., undergraduates) implementation of the Group‐Academic Mentoring Program for Education Development (Group‐AMPED) to school psychology graduate students' implementation of Group‐AMPED. Ten paraprofessionals and five school psychology graduate students provided approximately eight sessions of Group‐AMPED to 35 sixth‐grade students. Results indicated no significant differences between middle school students' engagement when groups were led by either school psychology graduate students or paraprofessionals. Similarly, self‐reports of fidelity and supervisor postsession implementation confidence indicated no difference between paraprofessionals and graduate students' implementation of Group‐AMPED. Follow‐up measures indicated that mentors and proteges perceived Group‐AMPED as feasible, acceptable, and understandable. Most importantly, middle school students participating in Group‐AMPED had significantly higher second‐semester grades in comparison to a small control group.